Thirteen new records of marine invertebrates and two of fishes from Cape Verde Islands - Wirtz, Peter (2009)
The sea anemones Actinoporus elegans Duchassaing, 1850 and Anthothoe affinis (Johnson, 1861) are new records from Cape Verde Islands. Also new to the marine fauna of Cape Verde are an undescribed mysid species of the genus Heteromysis that lives in association with the polychaete Branchiomma nigromaculata, the shrimp Tulearicoaris neglecta Chace, 1969 that lives in association with the sea urchin Diadema antillarum, an undescribed nudibranch of the genus Hypselodoris, and two undescribed species of the parasitic gastropod genus Melanella and Melanella cf. eburnea. An undescribed plathelmint of the genus Pseudobiceros, the nudibranch Phyllidia flava (Aradas, 1847) and the parasitic gastropod Echineulima leucophaes (Tomlin & Shackleford, 1913) are recorded, based on colour photos taken in the field. The crab Nepinnotheres viridis Manning, 1993 was encountered in the bivalve Pseudochama radians, which represents the first host record for this pinnotherid species. The nudibranch Tambja anayana, previously only known from a single animal, was reencountered and photographed alive. The sea anemone Actinoporus elegans, previously only known from the western Atlantic, is also reported here from São Tomé Island. In addition, the bythiid fish Grammonus longhursti and an undescribed species of the genus Apletodon are recorded from the Cape Verde Islands for the first time.